HER2 amplification in tumors activates PI3K/Akt signaling independent of HER3 - Ruiz-Saenz, Ana (Cancer Res, 2018)
Current evidence suggests that HER2-driven tumorigenesis requires HER3. This is likely due to the unique ability of HER3 to activate PI3K/Akt pathway signaling, which is not directly accessible to HER2. By genetic elimination of HER3 or shRNA knockdown of HER3 in HER2-amplified cancer cells, we find residual HER2-driven activation of PI3K/Akt pathway signaling that is driven by HER2 through direct and indirect mechanisms. Indirect mechanisms involved second messenger pathways including Ras or Grb2. Direct binding of HER2 to PI3K occurred through p-Tyr1139, which has a weak affinity for PI3K but becomes significant at very high expression and phosphorylation. Mutation of Y1139 impaired the tumorigenic competency of HER2. Total elimination of HER3 expression in HCC1569 HER2-amplified cancer cells significantly impaired tumorigenicity only transiently, overcome by subsequent increases in HER2 expression and phosphorylation with binding and activation of PI3K. In contrast to activation of oncogenes by mutation, activation by overexpression was quantitative in nature: weak intrinsic activities were strengthened by overexpression, with additional gains observed through further increases in expression. Collectively, these data show that progressive functional gains by HER2 can increase its repertoire of activities such as the activation of PI3K and overcome its dependeny on HER3.